Sleep pattern, obesity and healthcare expenditures in Brazilian adults - Silva, Eduardo Pereira da [UNESP]; Rodrigues Rocha, Ana Paula; Castanho Araujo, Monique Yndawe [UNESP]; Turi, Bruna Camilo; Fernandes, Romulo Araujo [UNESP]; Codogno, Jamile Sanches [UNESP] (Abrasco-assoc Brasileira Pos-graduacao & Saude Coletiva, 2019)
The aim of this study was to analyze the relationship between sleep pattern and healthcare expenditures in adults, as well as to identify whether physical activity, biochemical markers and obesity affect this relationship. The sample was composed of 168 adults aged >= 50 years attended by two Basic Healthcare Units in Presidente Prudente, SP, Brazil. Health expenditure, sleep pattern, anthropometry, adiposity index, physical activity, metabolic and cardiovascular variables were assessed. Statistical analyses were performed using Kruskal-Wallis, Mann-Whitney and Spearman tests. Sleep disorders were positively correlated to higher costs with medicines and negatively correlated to costs with laboratory tests, even after adjusts by confounders. In addition, healthcare costs were also correlated to physical activity score, blood pressure, obesity and metabolic variables. Severe sleep disorders and high percentage of body fat were associated with increased use of medications. Sleep pattern is correlated to primary care healthcare costs, obesity and physical activity level.
Keywords: Healthcare costs; Sleep wake disorders; Body fat distribution